Molecular aspects of esophageal squamous cell carcinoma carcinogenesis - Lehrbach,Dárcio Matenhauer (2003)
BACKGROUND: The development of human esophageal cancer is a multistep, progressive process. An early indicator of this process is an increased proliferation of esophageal epithelial cells morphologically including basal cell hyperplasia, dysplasia, carcinoma in situ and advanced esophageal squamous cell carcinoma. The process of tumorigenesis at cellular level is related to disorders of the control of cell proliferation and differentiation and controlled cell death (apoptosis). Most of cancer cells contain genetic alterations related to the control of these processes, including transcription factors and apoptosis related proteins. AIM: In this review, the current knowledge of the genetic profile of this subtype of esophageal tumor is discussed, focusing on the potential of the development of novel tools for clinical management of esophageal squamous cell carcinoma. CONCLUSIONS: The advances in the field of molecular biology have let us to deeper our knowledge of the process of carcinogenesis of esophagus. Ideally, this knowledge should be translated in benefits for patients suffering from cancer. Thus, better understanding of molecular alterations during carcinogenesis is expected to improve tumor control and prevention and also may lead to better disease management.